PP23 Simulated anaesthetic scenarios: a novel approach to improve access to anaesthetic simulation training. (10th November 2020) - Nussbaum, Gregory; Smith, Dominic; Trimble, Alice; Harrison, Richard; Wiggins, Jessica; Faculty, SAS
Abstract : Introduction: There is no single, online resource providing filmed, simulated anaesthetic scenarios. The impact of the COVID-19 pandemic on face-to-face training is already apparent. Educational research supports the use of complimentary visual aids and, specifically, video to enhance learning of written information. It is well established that simulation, and particularly team simulation, improves patient safety and is necessary in the implementation of guidelines. To address the inevitable shift to online courses, we have created a free, innovative, online library of realistic, simulated scenarios 1 filmed at Royal Bournemouth Hospital (RBH) and adhering to national guidelines. Project Description: The Theatre Simulation Faculty at RBH have developed a freely accessible website 1 populated with videos of simulated anaesthetic scenarios. The simulations are filmed in theatre, they are unscripted and designed to be as realistic as possible. A 'lifecast' model is used to increase the fidelity of the simulation. Scenarios are created to follow national guidelines such as those set out in the AAGBI Quick Reference Handbook 2 . Initial videos cover the management of general anaesthetic emergencies but future videos will cover sub-specialties such as paediatrics and obstetrics, aim to support novice training, provide resources for doctors returning to work after periods of absence and also be used to compliment operating department practitioner and physician assistant training. The website has been publicised via social media and through the Wessex Deanery. The website is also listed as a simulation resource by the Royal College of Anaesthetists 3 . To measure opinion on the first wave of videos released, a group of Wessex anaesthetic trainees of various levels were surveyed. Results: 64% of trainees surveyed found it easier to learn a guideline through simulation than through reading alone. Of these same trainees, 45% claim to have no regular access to simulation training and, of those who do, 66% are finding it harder to access simulation training since the arrival of COVID-19. All of those surveyed found the videos 'useful' or 'very useful' as an adjunct to learning guidelines for emergency management in anaesthesia. This initial feedback supports the usefulness of video to improve online learning and to embed emergency protocols particularly at a time when face-to-face learning is restricted. Discussion and Conclusion: The team have been approached to create specific videos to assist in the delivery of online courses and plan to continue to expand the library of videos alongside the delivery of in-situ theatre team training at RBH. References: Simulated Anaesthetic Scenarios:https://www.sashealthcare.solutions AAGBI Quick Reference Handbook: https://anaesthetists.org/Quick-Reference-Handbook Royal College of Anaesthetists – simulation resources: https://rcoa.ac.uk/simulation-resources